2023
DOI: 10.1155/2023/9094092
|View full text |Cite|
|
Sign up to set email alerts
|

miR-141-3p Targeted SIRT1 to Inhibit Osteogenic Differentiation of Bone Marrow Mesenchymal Stem Cells

Abstract: Purpose. To explore the expression of miR-141-3p during the osteogenic differentiation of human bone marrow mesenchymal stem cells (BMSCs) and its regulatory effect. Methods. Differentiation of BMSCs was induced by dexamethasone. The mRNA expression of miR-141-3p, ALP, RUNX2, and OCN was measured using RT-qPCR. The protein expression was detected via western blot. The target of miR-141-3p was predicted through the TargetScan website and confirmed using luciferase reporter assay. Results. miR-141-3p expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although there is no study regarding how tFNA regulates SIRT1/FoxO1 expression currently, other related signaling pathways may be involved according to the available reports. For instance, SIRT1 is closely associated with Wnt/β-catenin signaling pathways, which could also be activated by tFNAs, , the synergy of SIRT1 and Wnt pathway has been extensively investigated in various cell lines and disease models. , Moreover, FoxO proteins compete for the binding sites of β-catenin with a T-cell transcription factor. The overexpression of FoxO proteins could inhibit the Wnt/β-catenin signaling pathway in the case of oxidative stress or senescence. , Thus, the Wnt/β-catenin pathway may be a bridge between SIRT1 and FoxO1, the detailed mechanism still requires further exploration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no study regarding how tFNA regulates SIRT1/FoxO1 expression currently, other related signaling pathways may be involved according to the available reports. For instance, SIRT1 is closely associated with Wnt/β-catenin signaling pathways, which could also be activated by tFNAs, , the synergy of SIRT1 and Wnt pathway has been extensively investigated in various cell lines and disease models. , Moreover, FoxO proteins compete for the binding sites of β-catenin with a T-cell transcription factor. The overexpression of FoxO proteins could inhibit the Wnt/β-catenin signaling pathway in the case of oxidative stress or senescence. , Thus, the Wnt/β-catenin pathway may be a bridge between SIRT1 and FoxO1, the detailed mechanism still requires further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, SIRT1 is closely associated with Wnt/β-catenin signaling pathways, which could also be activated by tFNAs, 19,26 the synergy of SIRT1 and Wnt pathway has been extensively investigated in various cell lines and disease models. 48,49 Moreover, FoxO proteins compete for the binding sites of β-catenin with a T-cell transcription factor. The overexpression of FoxO proteins could inhibit the Wnt/βcatenin signaling pathway in the case of oxidative stress or senescence.…”
Section: Tfna-enhanced Osteogenesis and Angiogenesis Of The Callus At...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%